Assessment of Children with Cerebral Palsy Using Common Brief Core Set of International Classification of Functioning, Disability and Health for Children and Youth (ICF-CY) - Hina, Ammara; Maqbool, Shazia; Azhar, Hina; Fatima, Saba; Farid, Aisha; Ullah, Ehsan (Pakistan Armed Forces Medical Journal, 2023)
Objective: To assess children with cerebral palsy using the Common Brief Core Set of International Classification of Functioning, Disability and Health for Children and Youth (ICF-CY).Study Design: Cross-sectional studyPlace and Duration of Study: Children Hospital & Institute of Child Health, Lahore Pakistan, from Nov 2020 to Jan 2021.Methodology: Fifty-nine children with cerebral palsy (CP) aged 0-18 years were included. Common Brief Core Set of International Classification of Functioning, Disability, and Health in Children and Youth (ICF-CY) was administered to children with cerebral palsy to assess their functional status. Strengths and weaknesses in body structure, body function,activity and participation and environmental factors were evaluated using the Common Brief Core Set of ICF-CY. Results: The majority of study participants were 38(64.4%), were spastic quadriplegic. Periventricular leukomalacia was noted in 36(67.9%) cases on MRI brain. Moderate to severe impairment was noted in body functions like intellectual function 46(78%). In addition, 26(44.1%) children with cerebral palsy had mild to moderate impairment in walking, while 4(6.8 %) could walk without any impairment. Social attitudes, construct, and design of buildings were the major barriers affecting the functionality of children with cerebral palsy.Conclusion: It was found that the Common Brief Core Set of ICF-CY in children with different types of cerebral palsy is a useful tool for assessing their functional level.Keywords: Cerebral Palsy, Common Brief Core Set, Disability, Health in Children and Youth (ICF-CY), International Classification of Functioning.